Perceptions and experiences of primary school teachers in teaching critical thinking in Grade 6 Social Sciences - Mudau, Edwin (My University, 2020)
The purpose of this study was to explore primary school teachers’ perceptions and experiences in teaching critical thinking in grade six Social Sciences. In its aims, the Curriculum and Assessment Policy Statement (CAPS) indicates that teachers in the Intermediate Phase must engage learners in critical thinking. This study comprised of three participants drawn from three purposively selected schools: one township, one independent and one former model C school. All the primary schools are located in the Gauteng Province of the Republic of South Africa. All participants had been teaching Social Sciences for more than three years. This study was based on a qualitative research approach and a case study design was employed. Data collection was done through conducting semi-structured interviews and analysis of formal assessment tasks set by the participants for summative assessment purposes. The analysis of data followed a thematic analysis approach. The Revised Bloom’s Taxonomy was used as an instrument to evaluate the teaching of critical thinking by participants. The findings indicated that the teaching and assessment were biased towards low order cognitive skills. Teachers were not teaching for critical thinking and that there was no deliberate focus on the teaching of critical thinking in primary schools by both teachers and school management teams. Teachers did not include high-level cognitive ability questions in their assessments and as a result, the marks recorded did not reflect high-quality learning, implications include that performance analysis of primary schools needs to be reviewed to prioritise quality teaching and learning. Finally, this study recommended that district offices develop a framework for tracking the teaching of critical thinking.
A research report submitted n fulfilment of the requirements of the degree of Master of Education to the School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020
Keywords: Thought and thinking--Study and teaching (Elementary); Critical thinking--Study and teaching; Creative thinking in children--Study and teaching